New fluorinated aromatic polyamides based on N, N-bis(4-carboxyphenyl)-4-trifluoromethylaniline. (August 2019) - Zhou, Yu-Ting; Huang, Zhen-Zhong; Song, Cheng; Tang, Chuan-Chao; Liu, Xiao-Ling; Sheng, Shou-Ri
A new aromatic diacid monomer, N, N -bis(4-carboxyphenyl)-4-trifluoromethylaniline, was synthesized by the substitution reaction of 4-trifluoromethylaniline with 4-fluorobenzonitrile, followed by alkaline hydrolysis of the dinitrile intermediate. Several polyamides with 4-trifluoromethyltriphenylamine moieties were prepared from the diacid and various aromatic diamines via the direct phosphorylation polycondensation. All the polyamides were amorphous and readily soluble in many polar organic solvents such as N, N -dimethylacetamide and N -methyl-2-pyrrolidone, and could be solution-cast into transparent, tough, and flexible films with good mechanical properties. They exhibited good thermal stability with glass transition temperatures of 260–330°C, 10% weight-loss temperatures above 500°C, and char yields higher than 60% at 800°C in nitrogen. These polymers had low dielectric constants of 3.35–3.72 (100 Hz), low water uptake of 1.80–2.60%, and high transparency with an ultraviolet–visible absorption cutoff wavelength in the range of 378–390 nm. Cyclic voltammograms of the polyamide films cast onto an indium-tin oxide–coated glass substrate exhibited a reversible oxidation redox coupled with oxidation half-wave potentials ( E 1/2 ) of 0.95–1.04 V versus silver/silver chloride in an acetonitrile solution.